2019
DOI: 10.3390/cells8040308
|View full text |Cite
|
Sign up to set email alerts
|

Time- and Kellgren–Lawrence Grade-Dependent Changes in Intra-Articularly Transplanted Stromal Vascular Fraction in Osteoarthritic Patients

Abstract: Knee osteoarthritis (OA) is one of the most prevalent disorders in elderly population. Among various therapeutic alternatives, we employed stromal vascular fraction (SVF), a heterogeneous cell population, to regenerate damaged knee cartilage. OA patients were classified on the basis of age, gender, body mass index (BMI), and x-ray-derived Kellgren–Lawrence (KL) grade. They were treated with SVF and followed-up for 24 months. Visual analogue scale (VAS) and Western Ontario and McMaster Universities Osteoarthrit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(100 citation statements)
references
References 75 publications
2
97
1
Order By: Relevance
“…These observations imply that, overall, patients with lower-grade osteoarthritis may have a higher probability of benefitting from the treatment with the SVF. Tran et al found a better improvement after intra-articular SVF injection in patients with grade 3 OA compared with patients with grade 2 OA [16]. In that case, the patient group with higher-grade OA benefited most from the treatment.…”
Section: Pearson Correlation Coefficient (R)mentioning
confidence: 97%
See 1 more Smart Citation
“…These observations imply that, overall, patients with lower-grade osteoarthritis may have a higher probability of benefitting from the treatment with the SVF. Tran et al found a better improvement after intra-articular SVF injection in patients with grade 3 OA compared with patients with grade 2 OA [16]. In that case, the patient group with higher-grade OA benefited most from the treatment.…”
Section: Pearson Correlation Coefficient (R)mentioning
confidence: 97%
“…Whether the injected cells of the SVF in fact contribute to the actual regeneration of the cartilaginous tissue remains yet to be fully elucidated. While some studies reported a quantifiable regeneration of cartilage [ 8 , 15 , 16 ], others did not observe any changes [ 17 , 18 ]. Even if the de novo formation of the cartilaginous tissue can be documented, the following questions remain: What type of cartilage has been formed?…”
Section: Introductionmentioning
confidence: 99%
“…The results suggest that the most pronounced improvement occurs between the third and sixth months, but the assessments used are subjective, and we believe that drawing conclusions on this aspect could be premature. Other studies have reported an extended follow-up period of 2 years [29], finding similar positive results, although they suggest that efficacy may decrease after this initial period of treatment. There are still many questions to answer, such as the possibility of optimizing the therapeutic effect with repeated doses, the influence of cell dose used, or the possibility of testing different routes of administration, among others.…”
Section: Svf Characterizationmentioning
confidence: 60%
“…179 SVFs have been tested as promising healing approach in OA. 17,185 SVF fraction acts submit your manuscript | www.dovepress.com…”
Section: Cell-based Approaches In Oa: Mscsmentioning
confidence: 99%